2015
DOI: 10.1002/eji.201545554
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand‐expressing recombinant vaccinia virus promotes the generation of CD8+ central memory T cells

Abstract: Central memory CD8 + T cells (T CM ) play key roles in the protective immunity against infectious agents, cancer immunotherapy, and adoptive treatments of malignant and viral diseases. CD8+ T CM cells are characterized by specific phenotypes, homing, and proliferative capacities. However, CD8 + T CM -cell generation is challenging, and usually requires CD4 + CD40L + T-cell "help" during the priming of naïve CD8 + T cells. We have generated a replication incompetent CD40 ligand-expressing recombinant vaccinia v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…þ T cells following 72-hour culture by flow cytometry (28). IFNg release in culture supernatants was assessed by using commercial ELISA Kits (BD Biosciences).…”
Section: Neutrophil and Cd8mentioning
confidence: 99%
“…þ T cells following 72-hour culture by flow cytometry (28). IFNg release in culture supernatants was assessed by using commercial ELISA Kits (BD Biosciences).…”
Section: Neutrophil and Cd8mentioning
confidence: 99%
“…It has been reported that the use of surgifoam induces a CD40-CD40L interaction to augment effector CD8 + T-cell function [29]. Activation of co-stimulatory molecules is important in the induction of the adaptive immune response, and it plays a significant role in the development of CD8 + T-cell memory response and cross-presentation of MHC-I restricted antigen [30-32]. It is likely that the surgifoam may serve as an adjuvant augmenting CD8 + T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their recruitment might represent a critical step in the elicitation of antitumor immune responses. [28][29][30] CXCR3 chemokine receptor is expressed in CD8+ lymphocytes, and, preferentially, in "central memory" T cells, characterized by marked antitumor potential 17,31 (Supplementary Figure 4a). While CXCR3 ligands include CXCL9, CXCL10, and CXCL11, the main role in CD8+ T cells recruitment has been attributed to CXCL10.…”
Section: Cd40-stimulated M1-and M2-like Macrophages Promote the Recrumentioning
confidence: 99%
“…Due to these characteristics and its safety, VV has been used in recombinant form (rVV) in a variety of cancer immunotherapy protocols. [14][15][16][17][18] In particular, rVVs have successfully been used to induce T-cell responses specific for tumor-associated antigens (TAAs) in patients bearing cancers of different histological origins. 15,18 Moreover, rVVs have also been used as oncolytic reagents upon systemic or intratumoral administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation